Influence of Parental Involvement on Reading Proficiency among Early Childhood Students in South Africa - Nkosi, Mandla (American Journal of Education and Practice, 2024)
Purpose: The aim of the study was to assess the influence of parental involvement on reading proficiency among early childhood students in South Africa. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found significant acorrelations between parental involvement and children's reading skills. Findings revealed that children whose parents actively engaged in reading-related activities, such as reading aloud, providing books at home, and frequent visits to libraries, demonstrated higher levels of reading proficiency compared to those with less parental involvement. Furthermore, the study highlighted the importance of early interventions and consistent parental support in fostering literacy skills during the formative years of a child's development. Implications to Theory, Practice and Policy: Social-cultural theory, ecological systems theory and self-determination theory may be used to anchor future studies on assessing the influence of parental involvement on reading proficiency among early childhood students in South Africa. Educational institutions and community organizations should prioritize the implementation of parent education programs aimed at equipping parents with the knowledge, skills, and resources necessary to support their children's literacy development. Policymakers should prioritize the integration of parental involvement initiatives within early childhood education policies and frameworks.